Determinants of QRIS Adoption Intention for MSMEs: Identification During Covid-19 - Erlinda Sholihah; Risma Nurhapsari (Universitas Kristen Indonesia Toraja, 2022)
The purpose of this study is to examine the role of product knowledge, perceived benefit, and perceived ease of use on QRIS adoption intention for MSMEs in Semarang City during the Covid-19 pandemic. An associative quantitative approach was applied in this study. Population of this research are merchants in Semarang City’s traditional market. Empirical data were collected through questionnaires from 100 respondents and analyzed with SmartPLS 3.0 based on the SEM-PLS method. The results of this study confirm that product knowledge, perceived benefit, and perceived ease of use have a significant impact on the intention to adopt QRIS. The findings encourage the government to continue to accelerate the formation of a cashless society and increase public awareness of the benefit of digital payments in preventing the spread of the virus, especially the use of QRIS.